Association of Medicaid Expansion With Neuraxial Labor Analgesia Use in the United States: A Retrospective Cross-Sectional Analysis. Issue 3 (24th September 2022) - Xiao, M.; Whitney, D.; Guo, N.; Sun, E.; Wong, C.; Bentley, J.; Butwick, A.
Abstract : ( Anesth Analg . 2022;134:505–514) Before 2010, 1 in 4 women and 1 in 8 pregnant women were uninsured. The United States' Patient Protection and Affordable Care Act enacted in 2010 aimed to insure these uninsured individuals and families by increasing Medicaid coverage. The number of states observing this act, as it is optional, has increased from 26 in 2014 to 38 in 2021. While Medicaid expansion increased coverage for prenatal care and childhood, Medicaid's effect on neuraxial labor analgesia use is unclear. Previous studies show lower pain scores, and higher patient satisfaction scores are linked with neuraxial analgesia for the 75% of women who receive it. Localized labor analgesia minimizes general anesthesia risks, including airway complications, postoperative pain, and neonatal resuscitation. This study analyzes the effects of Medicaid expansion on neuraxial labor analgesia use since its adoption.